KEBERADAAN MANUSIA DALAM PERSPEKTIF MARTIN HEIDEGGER - A., Agustianto (Universitas Lancang Kuning, 2013)
According to Martin Heidegger humans 'existence in the world deals with dual conditions: Being in the world and controlling the world. In daily life phenomenologically humans have practical relation. The way humans exist is called exisience. Humans 'existence is described in two models, they are unreal and real human existence.